TINGKAT KEPATUHAN ANTIHIPERTENSI DAN PENGONTROLAN TEKANAN DARAH PASIEN RAWAT JALAN RS PKU MUHAMMADIYAH BANTUL, YOGYAKARTA YANG MENDAPATKAN BRIEF COUNSELING-5A DAN SMS MOTIVASIONAL - Zukhruf Ginanjar Saputri; Akrom Akrom; Endang Darmawan (Sanata Dharma University, 2016)
Antihypertensive therapy requires adherence therapy to achieve therapeutic targets such as controlling blood pressure both systolic and diastolic blood pressure. Pharmacists in counseling interventions have been developed in the form of brief Counseling - 5A and SMS reminders. But the relationship between adherence and blood pressure control is still studied and both of them are related to many factors that can affect. The aim of this study was to determine the relationship of the level of compliance antihypertensive therapy and control of blood pressure (systolic and diastolic) hypertension patients in outpatient PKU Muhammadiyah Bantul, Yogyakarta who get Brief counseling - 5A and SMS motivation.Patients who met the inclusion criteria were divided into 2 groups, the treatment group (n = 30) who received Brief counseling - 5A and SMS motivation, and the control group (n = 30) who received usual care (conventional counseling). Data were collected by interviews using questionnaires compliance of Morisky Medication Adherence Scale (MMAS), the value of blood pressure is taken from the medical record. Correlation between level of adherence and blood pressure control have been analyzed using Fisher test. The results showed the treatment group with categories adherent patients (n=25) was increase in blood pressure control by 36.67% compared with the control group of patients adherent category (n=6) only 6.67% that has control of the blood pressure on post study. In contrast to patient with adherent category, who had uncontrolled blood pressure are 46.67% (treatment group) compared to the control group 13.33% on the post study. Patients categories of non-adherent but is having control of blood pressure showed 3.33% (treatment group) and 26.67% (control group) on the post study. Although the rate of compliance in the treatment group was higher than control group on the second visit, but there was no significant relation between the level of compliance and controlling blood pressure both in control group (p=1.000) and intervention group (p=0.622) on the second visit (post). The rate of compliance and blood pressure control of patients with hypertensive was low. There were many factors such as poor of knowledge, drugs side effect, poly pharmacy, which related with level of compliance. There was no correlation between antihypertensive compliance and blood pressure control in hypertensive patients ambulatory PKU Muhammadiyah Bantul Hospital, who get Brief counseling 5A and SMS motivation. Therefore it is necessary to do further research to identify factors that influence to improve patients awareness in the management of hypertension.